2020
DOI: 10.1177/0959683620941096
|View full text |Cite
|
Sign up to set email alerts
|

Dramatic recent changes in small mammal assemblages from Northern Patagonia: A caution for paleoenvironmental reconstructions

Abstract: Temporal differences in fossil assemblages of small mammals can generate important insights into associated environmental conditions. Moreover, by including modern assemblages in such comparisons, it may also be possible to identify the effects of recent human colonization on mammal communities and their habitats. To explore potential signals of European colonization in northwestern Patagonia, we compared fossil and modern assemblages of small mammals from two newly characterized paleontological sites in the L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 77 publications
(108 reference statements)
1
21
0
Order By: Relevance
“…rosiae. Likewise, other archaeological (Pearson and Pearson 1993;Teta and Ortiz 2002;Bernardis et al 2013;Fernández et al 2016;Tammone et al 2020) and paleontological (Verzi et al 2002) sites with records of living octodontid genera show that especially the cis-Andean (east of the Andes) representatives of this family are often nondominant species in their communities (see Ojeda 2010). Thus, if timetrees recovered to date are correct, early representatives of current octodontids could also have been rare species in their communities (see Vrba and DeGusta 2004) and in this case, their absence from the fossil record could be the result of taphonomic biases, including problems of geographic representation that are inherent in the archaeological and paleontological record.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…rosiae. Likewise, other archaeological (Pearson and Pearson 1993;Teta and Ortiz 2002;Bernardis et al 2013;Fernández et al 2016;Tammone et al 2020) and paleontological (Verzi et al 2002) sites with records of living octodontid genera show that especially the cis-Andean (east of the Andes) representatives of this family are often nondominant species in their communities (see Ojeda 2010). Thus, if timetrees recovered to date are correct, early representatives of current octodontids could also have been rare species in their communities (see Vrba and DeGusta 2004) and in this case, their absence from the fossil record could be the result of taphonomic biases, including problems of geographic representation that are inherent in the archaeological and paleontological record.…”
Section: Discussionmentioning
confidence: 98%
“…The crown clade Octodontidae differentiated in southern South America during the Late Miocene, over 10 My later than the divergence of the total clade Octodontidae from their sister family Ctenomyidae (Upham and Patterson 2012, 2015; Verzi et al 2014, 2016; Álvarez et al 2017). The time-calibrated phylogenies show that crown genera were already differentiated in the Pliocene (Table 1), yet their fossil record is limited mostly to the latest Pleistocene–Holocene (Massoia et al 1981; Simonetti 1989, 1994; Pearson and Pearson 1993; Massoia and Silveira 1996; Simonetti and Saavedra 1998; Teta and Ortiz 2002; Saavedra and Simonetti 2003; Saavedra et al 2003; Udrizar Sauthier et al 2009; Fernández et al 2016; López et al 2016; Labarca et al 2020; Tammone et al 2020). As an exception, Tympanoctomys is recorded in the Early Pleistocene (Ameghino 1889; Verzi et al 2002); in addition, Ameghino (1891) reported presence of Aconaemys in the “Pampeano inferior” (Pleistocene) of Córdoba based on mandibular remains and isolated teeth—these specimens being currently missing from the paleontological MACN collection.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent forest declination in south Lago Argentino mostly has been connected with the effects of global climatic events of short duration (e.g., Cerro Frías; Mancini, 2009). In any case, the marked current abundances of Oligoryzomys longicaudatus and L. micropus in Cerro Benítez can be connected with forest clearance and with concomitant shrubland expansion (see Tammone et al, 2020).…”
Section: Holocene Environmental Evolution In Cerro Benítez: Integrating Biological Evidencementioning
confidence: 99%
“…Several researchers (Green & Osborne, 2003; Happold, 2008; Menkhorst, 1995; Menkhorst et al, 2008; Ride, 1956; Schulz et al, 2019; Watts & Aslin, 1981) attribute the wider distribution of M. fuscus in the past to the cooler conditions of the late Pleistocene, which are thought to have been more suitable for the species, and propose that the modern distribution of M. fuscus has been limited by climate change. However, recent radiometric dating has shown many of the fossil deposits containing M. fuscus accumulated during the Holocene (Table S2), This suggests the species suffered a rapid range contraction in response to anthropogenic ecosystem modifications following European settlement (rather than climate change; Fusco et al, 2015; Tammone et al, 2020). Because these threatening processes continue, M. fuscus will probably experience ongoing declines unless conservation management actions are undertaken (Bilney et al, 2010; Green et al, 2008; Green & Osborne, 2003; Happold, 2008; Hocking & Driessen, 2000; McDowell, 2013; Menkhorst, 1995; Menkhorst et al, 2008; Seebeck, 1971; Seebeck & Menkhorst, 2000).…”
Section: Introductionmentioning
confidence: 99%